The Fatimid Educational administration in Egypt - Ramdane, Tahraoui; Souad, Merah (Centre for Promoting Ideas, USA, 2014)
This paper tries to investigate the Fatimid educational administration experience in Egypt. It starts by reviewing the historical conditions that paved the way for the establishment of this Ismā’īli state, as well as the principal foundations of their ideology. This is significant, because in medieval Islam administration of educational activities was part of an interconnected bureaucracy, in which education, religious sectarian preferences and politics were inseparable. Writing about the Fatimid educational administration is always difficult because the Fatimid political apparatus’s nature, and the wide spread culture of secrecy. What makes the matter more complicated is the style of recording events by Muslim historians of that era. They followed a methodology which chronicled the political, religious and economic aspects of life on annual basis, and neglected other aspects such as educational administration. Concepts related to modern educational administration literature like centralization, unity of command, span of control and merit, were rarely mentioned in the historical sources. These difficulties made this research a testing challenge.